Epoxidation of Acrylic Acid by Tetraethylammonium Chlorochromate in an Aquo-Acetic Acid-A Kinetic Study - Awasthi, Anupam; Singh, J.V.; Dipti (Asian Journal of Chemistry, 2010)
Tetraethylammonium chlorochromate oxidised acrylic acid in aqueous acetic acid (50 % v/v) medium in presence of perchloric acid to the epoxide as the oxidation product. The rate of the reaction was dependent on the first power of the concentration of oxidant, substrate and acid. Ionic strength variation has no effect on the reaction rate. The reaction does not induce polymerization. The reaction rate increased with increasing amount of acetic acid in the mixture. Thermodynamic and activation parameters for the reaction have been computed from the data on the temperature dependence. A suitable mechanism consistent with the observed kinetic results has been postulated.